2007
DOI: 10.1016/j.virol.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Novel porcine rotavirus of genotype P[27] shares new phylogenetic lineage with G2 porcine rotavirus strain

Abstract: A novel and unusual strain of porcine rotavirus (PoRV) CMP034 was isolated from a 7-week-old piglet during the epidemiological survey of porcine rotavirus infection in Chiang Mai province, Thailand from June 2000 to July 2001. Molecular characterization of gene VP4 by sequence analysis showed a low level of amino acid sequence identity, ranging from 56.7% to 76.6%, while comparison of VP8* portion showed 41.8% to 69.9% identity, with the 26 P genotypes recognized to date. Phylogenetic analysis of the VP4 seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(102 citation statements)
references
References 41 publications
3
95
0
4
Order By: Relevance
“…We detected the recently described new rotavirus genotype P[27] in 11.1 % of all positive samples. It is interesting that, in this and other studies, the P[27] genotype was found in four G/P combinations: G1, G2-like, G4 (this study) and G5 (Khamrin et al, 2007;Martella et al, 2007;Steyer et al, 2007a). The rotavirus P[27] genotype strains (CMP034, 344/04-1 and P21-5) independently detected by these three author groups showed high genetic variability, as they shared only 89-90.8 % VP4 amino acid sequence identity within this genotype.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…We detected the recently described new rotavirus genotype P[27] in 11.1 % of all positive samples. It is interesting that, in this and other studies, the P[27] genotype was found in four G/P combinations: G1, G2-like, G4 (this study) and G5 (Khamrin et al, 2007;Martella et al, 2007;Steyer et al, 2007a). The rotavirus P[27] genotype strains (CMP034, 344/04-1 and P21-5) independently detected by these three author groups showed high genetic variability, as they shared only 89-90.8 % VP4 amino acid sequence identity within this genotype.…”
Section: Discussionsupporting
confidence: 59%
“…The most prevalent rotavirus genotypes in pigs were G3P[6] (15 samples, 18.5 %), G4P[6] (ten samples, 12.3 %) and G5P [7] (11 samples, 13.6 %). The recently recognized rotavirus genotype P[27] (Khamrin et al, 2007;Martella et al, 2007;Steyer et al, 2007a) was found in nine (11.1 %) samples and was combined with three different G types: G1, G2 and G4 (Table 4).…”
Section: Incidence Of Group a Rotaviruses In Human And Animal Stool Smentioning
confidence: 99%
See 1 more Smart Citation
“…E1 is the predominant genotype in most parts of the world followed by E2. Some other uncommon genotypes like E6 and E9 have also been reported from a few geographical areas (Khamrin et al, 2007;Rehman et al, 2007).…”
Section: Genotypes and Dendogrammentioning
confidence: 95%
“…These antigens are responsible for conferring immunity and hence are a target for vaccine development. Although 15 different G serotypes and 27 P genotypes [8][9][10][11] have been detected in humans, serotypes G1P [8], G2P [4], G3P [8], G4P [8] and G9P [8] are thought to be important causes of diarrhea in infants and young children worldwide. 12 The human astroviruses have been identified as one of the most frequent causes of infantile gastroenteritis, second in incidence only to rotavirus.…”
Section: Introductionmentioning
confidence: 99%